The Effects of Inspiratory Muscle Training in Lung Cancer Patients: A Scoping Review - Kadir, Yolanda; Sabirin, Rahmaningsih Mara; Hasyim, Ammar Abdurrahman; Iqbal, Roihan Mohamad; Siswanto, Siswanto (Faculty of Medicine Universitas Airlangga, 2025)
Introduction: Lung cancer is the leading cause of cancer worldwide, with a high mortality rate. Chronic dyspnea promotes a pathologic cycle of decreased activity, which has been shown to limit exercise tolerance and deteriorate quality of life (QoL). Inspiratory muscle training (IMT) is a resistance-based exercise regimen that aims to improve the strength and endurance of the inspiratory muscles, thereby reducing respiratory symptoms. This study aimed to comprehensively review the possible beneficial effects of IMT on various aspects of lung cancer patients. Methods: The PubMed, Embase, and Cochrane databases were searched from inception to 20 May 2024. All clinical trials examining the impact of IMT on lung cancer patients, utilizing either quantitative or qualitative approaches, were included. The extracted data were then descriptively presented, focusing on the main themes to provide a comprehensive literature review. Results: This scoping review identified 9 unique studies comprising eight randomized-controlled trials and one retrospective cohort study with 460 lung cancer patients. An IMT regimen was proven to reduce sedentary behavior and significantly improve physical activity and health-related quality of life (HRQL). Furthermore, the IMT program reduced dyspnea, improving maximum inspiratory pressure (PImax) and 6-minute walking test (6MWT). It also provided the benefits of shorter postoperative stay and reduced patient distress concerning dyspnea. Conclusion: Inspiratory muscle training provides several benefits, including improvements in dyspnea indexes, exercise tolerance, and overall HRQL. Further studies are required to determine the optimal IMT regimen for this special population.